2011
DOI: 10.4037/ajcc2011810
|View full text |Cite
|
Sign up to set email alerts
|

As Health Care Technology Advances: Benefits and Risks

Abstract: Technology permeates every dimension of critical care. Bedside technology is integral to the assessment and monitoring of patients and to the provision of treatment. It also helps with access to vital information and can enhance commu nication. Although it offers extraordinary benefits to patients and clinicians, technology may also create problems. Our research addresses the wise use of technology in the care of critically ill patients. It examines the appropriate and safe use of technology, its equitable dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 18 publications
(13 reference statements)
0
9
0
Order By: Relevance
“…Advanced technology influences every aspect of critical care units and it is integral to the assessment and monitoring of patients and the treatment. It also helps to access vital information and enhances data communication (Funk, 2011). Critical care areas provide care for patients who need close observation and special treatment that cannot be provided in general wards.…”
Section: Coronary Care Unitsmentioning
confidence: 99%
“…Advanced technology influences every aspect of critical care units and it is integral to the assessment and monitoring of patients and the treatment. It also helps to access vital information and enhances data communication (Funk, 2011). Critical care areas provide care for patients who need close observation and special treatment that cannot be provided in general wards.…”
Section: Coronary Care Unitsmentioning
confidence: 99%
“…'s () study, they found that the integration of technology within nursing care was deemed good for the patient inasmuch that it reduced the need to disturb and unduly stress the patient especially when procedures needed to be undertaken such as blood sampling. Moreover, Price () in her ethnographic study suggested that there was a fine line between prioritizing patient care and attending to the technology, a similar thought found in Funk's () work where being seen as technically competent was the most visible way of demonstrating nursing care.…”
Section: Resultsmentioning
confidence: 99%
“…The importance of being safe and in control was noted by Alasad () and Kiekkas et al (), which links with the theme of vigilance; Burfitt et al () also identified this as important from the patients' perspective as they wanted to feel safe and observed. Using technology to closely observe the patient is still evident today but recognizes that a balance is needed (Funk, ). The role of prioritization and decision‐making as part of vigilance is not evident within the caring and technology literature but this may reflect the growing complexity of critical care practice where there is more focus on evidence‐based approaches.…”
Section: Discussionmentioning
confidence: 99%
“…This leads to a complex and confusing picture between the aesthetic and practical elements that entwine caring and technology within critical care practice (Burnard and Sandelowski, ). Carnevale () notes that caring is an invisible activity that is difficult to quantify and Funk () says that technology now permeates critical care and wonders if it is always used appropriately.…”
Section: Caring and Technology In Critical Carementioning
confidence: 99%